Training on Data Implementation From Transactions to Financial Reports at CV Geha Pratama: Pelatihan Implementasi Data Dari Transaksi Menjadi Laporan Keuangan Pada CV Geha Pratama - Tri Ayu Parwati; Olandari Mulyadi; Putri Azizi (KPN Kopertis X, 2022)
The socialization of the company's simple financial report is very much needed by many people, especially for the owner of the company as the initiator, the bank as the credit provider, and the government that provides facilities for the arrangement of laws and regulations, where each party has its own interests. Investors want to know the benefits of investment, banks want to know the level of security of loans provided and smooth returns, and the government is more focused on the benefits of these investments for the economy and equal distribution of employment opportunities. Application of financial reports regarding various transactions starting from identification and recording of transactions, recording transactions through general journals, posting ledgers, and transferring to trial balance. Until a company's financial statements are created. Financial reports The results can be used to make decisions about whether the business being run experiences a profit or loss, as well as an evaluation material for ongoing businesses, whether the financial records made are correct or not. In general, this business can be said to still use the traditional way of recording financial statements. Therefore, socialization and training are needed about the importance of recording financial statements in a company in a simple way.